Growth and Genetic Manipulation of Entamoeba histolytica. Issue 1 (27th January 2022) - Suleiman, Rene L.; Ralston, Katherine S.
Abstract: Entamoeba histolytica is a parasitic protozoan and the causative agent of amoebiasis in humans. Amoebiasis has a high incidence of disease, resulting in ∼67, 900 deaths per year, and it poses a tremendous burden of morbidity and mortality in children. Despite its importance, E. histolytica is an understudied parasite. These protocols describe the in vitro growth, maintenance, cryopreservation, genetic manipulation, and cloning of axenic E. histolytica trophozoites. There has been significant progress in genetic manipulation of this organism over the past decade, and these protocols outline the ways in which these advances can be implemented. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Culturing E. histolytica trophozoites Support Protocol 1 : Preparation of TYI‐S‐33 medium Support Protocol 2 : Lot testing of Biosate peptone and adult bovine serum for TYI‐S‐33 medium Basic Protocol 2 : Cryopreservation of E. histolytica trophozoites Support Protocol 3 : Preparation of cryoprotectant solutions Basic Protocol 3 : Transfection of E. histolytica trophozoites with Attractene reagent Basic Protocol 4 : Creating clonal lines using limiting dilution Basic Protocol 5 : Knockdown of one to two genes with trigger‐induced RNA interference Support Protocol 4 : Evaluation of RNA interference knockdown with reverse transcriptase PCR Basic Protocol 6 : E. histolytica growth curves